2014
DOI: 10.1063/1.4901333
|View full text |Cite
|
Sign up to set email alerts
|

The microstructural evolution of ultrananocrystalline diamond films due to P ion implantation process—the annealing effect

Abstract: The microstructural evolution of UNCD films which are P-ion implanted and annealed at 600 °C (or 800 °C) is systematically investigated. The difference of interaction that the UNCD content undergoes along the trajectory of the incident P-ions is reflected in the alteration of the granular structure. In regions where the P-ions reside, the “interacting zone,” which is found at about 300 nm beneath the surface of the films, coalescence of diamond grains occurs inducing nano-graphitic clusters. The annealing at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The compressive stress released thereby leads to higher carrier concentration which also leads to lowering of the Hall mobility. In a different study on phosphorus implanted UNCD films, it was found that for an implantation dosage of >10 14 ions cm −2 succeeded by 30 min annealing of the samples at 800 • C decreased the electrical resistivity but surprisingly did not improve the FEE behavior [48,49]. At around 300 nm below the surface of the film where the implanted phosphorus ions reside the granular structure gets altered, the diamond grains coalesce and nanographitic clusters form channels for charge carrier transport.…”
Section: Ion Implantation Of Nitrogen and Other Non-metallic Species ...mentioning
confidence: 99%
“…The compressive stress released thereby leads to higher carrier concentration which also leads to lowering of the Hall mobility. In a different study on phosphorus implanted UNCD films, it was found that for an implantation dosage of >10 14 ions cm −2 succeeded by 30 min annealing of the samples at 800 • C decreased the electrical resistivity but surprisingly did not improve the FEE behavior [48,49]. At around 300 nm below the surface of the film where the implanted phosphorus ions reside the granular structure gets altered, the diamond grains coalesce and nanographitic clusters form channels for charge carrier transport.…”
Section: Ion Implantation Of Nitrogen and Other Non-metallic Species ...mentioning
confidence: 99%